Algoritmos para o problema de roteamento de veículos com cross-docking - Vinicius Wellington Coelho de Morais (2012)
This work addresses the Vehicle Routing Problem with Cross-Docking. Given a set of goods requests, a single Cross-Dock (CD), and several suppliers and customers, the problem consists in defining a minimum cost set of routes for a fleet of homogeneous vehicles that leaves the CD towards the suppliers, pickups the goods and returns to the initial point to perform the consolidation process. Thus, the same fleet of vehicles delivers the goods to the customers. The routes designed must respect the capacity constraints of the vehicles as well as the time windows constraints. We proposed three constructive heuristics, a heuristic based on the Iterated Local Search metaheuristic, and a matheuristic that integrates the latter and a Mixed Integer Programming model based on Set Partitioning. The heuristics were evaluated on instances from the literature and compared to the best existing heuristics for this problem. The results showed the efficiency of the implemented solutions.